2009
DOI: 10.1270/jsbbs.59.87
|View full text |Cite
|
Sign up to set email alerts
|

Variation in root morphology and anatomy among accessions of cultivated rice (Oryza sativa L.) with different genetic backgrounds

Abstract: Asian cultivated rice (Oryza sativa L.) has genetic diversification of root characteristics, but this variation has not been elucidated fully with reference to the genetic background. To clarify the differences in root anatomical and morphological traits among different varietal groups of cultivated rice, we analyzed four anatomical traits (root thickness, stele transversal area, total transversal area and number of late metaxylem vessels) and two morphological traits (root length index and ratio of deep rooti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
73
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 22 publications
1
73
1
Order By: Relevance
“…This plasticity enables plants to optimise the usage of the available soil volume, the supply of nutrient to the shoot and plant performance in general. Substantial diversity in RSA has been reported for several plant species including Arabidopsis (Pacheco-Villalobos and Hardtke 2012), rice (Uga et al 2009) and maize (Cai et al 2012). Root system traits of field-grown maize plants were evaluated using shovelomics and large variation was observed among genotypes across different years and environments (Trachsel et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This plasticity enables plants to optimise the usage of the available soil volume, the supply of nutrient to the shoot and plant performance in general. Substantial diversity in RSA has been reported for several plant species including Arabidopsis (Pacheco-Villalobos and Hardtke 2012), rice (Uga et al 2009) and maize (Cai et al 2012). Root system traits of field-grown maize plants were evaluated using shovelomics and large variation was observed among genotypes across different years and environments (Trachsel et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of naturally occurring phenotypic variations have been observed among rice (Oryza sativa L.) accessions, in both cultivars and their wild relatives (Jawahar and Panwar 1970, Matsuo 1952, McKenzie et al 1994, Mochida et al 2009, Quijano-Guerta et al 2002, Ueno et al 2009, Uga et al 2009). Analyses of molecular markers have also detected a considerable number of sequence variations in diverse cultivars (Sun et al 2002, Wang et al 1992, Yan et al 2007, Zeng et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the National Institute of Agrobiological Sciences (NIAS) have established two mini-core collections, each consisting of a small number of accessions that together cover more than 90% of the phenotypic and genotypic variation in rice accessions , Kojima et al 2005. These accessions have been used effectively for genetic analysis of quantitative traits and association mapping in rice (Iwata et al 2009, Ueno et al 2009, Uga et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Root distribution has also been quantitatively characterized by using several morphological traits, and wide genotypic differences have been detected (Nemoto et al, 1998;Kato et al, 2007;Uga et al, 2009). Although previous studies revealed genotypic differences in root development, information about the genotypic diversity of root traits and their response to osmotic stresses is limited because the employed cultivars do not fully cover a wide range of genetically diverse cultivars.…”
mentioning
confidence: 99%
“…Alternatively, the studies on genetic variations with the root system using RDRS are limited. Uga et al (2009) analyzed anatomical and morphological traits under rainfed upland conditions using RDRS, and found differences in root characteristics between japonica and indica accessions. Determining the responsible traits by using material with a wide genetic background may give essential information for further breeding strategies or genetic analysis.…”
mentioning
confidence: 99%